(untitled) (Research, Society and Development, 2021)
Anorexia Nervosa (AN) is an eating disorder that affects adults, young people and children, has a multifactorial etiology, characterized by a distortion of body image associated with fear of gaining weight, leading the individual to commit severe food restriction, causing extreme weight loss and malnutrition. This, clinical and metabolic manifestations associated with inflammatory biomarkers are triggered, based on evidence on the dysregulation of the immune system and an inflammatory immunomodudulation during AN. The present study aims to present evidence that demonstrates how inflammatory mediators are systematically related to the most common clinical manifestations more in AN. This is an integrative review, based on consultation of the databases: MEDLINE and LILACS. Sixteen studies were selected from 2014 to 2020 with 56, 25% NE3, followed by 31, 25% NE 5 and 12, 5% NE 2. Studies have shown that inflammatory biomarkers such as interleukins, and chemokines, leptin, ghrelin, omentine-1, adinonectin, BDNF, VEGF, VCAM, PCR, OC, CTX, OPG, RANK, RANKL, IFN -γ, NO, IGF and some classes of TNF are related to clinical manifestations in AN contributing to prolonged and difficult to reverse symptoms, such as depression, sleep disorders, memory and learning, altered behavior , tissue damage, decreased appetite, risk for cardiovascular disease, changes in the intestinal microbiome, osteoporosis, amenorrhea, inflammation of the hypothalamus, impaired energy metabolism and unregulated inflammatory state. However, further clarification is needed on this topic, as there are still few studies in this line of research.